Urf In The Charity Culture Perspective In Bima - Mega Oktaviany; Nadhirah Nordin; Rahimah Embong (LAA MAISYIR: Jurnal Ekonomi Islam, 2022)
The alms culture is an important phenomenon in improving the economic order in people's lives. Because, theoretically talking about almsgiving, will broaden the meaning because it has a law that is permissible, what is done is rewarded and what is not done has no impact whatsoever. However, when it is made into a culture, it will have a big impact, not only for individuals, but also for the whole society. The purpose of this study is to look at the practice of alms that is cultivated using the lens of Islamic law, namely 'urf. This type of research is descriptive qualitative, that is, apart from interviewing informants in the field, also from historical documents of the Bima kingdom. The result of this research is that there are four forms of almsgiving practices in Bima, namely sadaqa tara ne'e, alms tola bala, alms kaneo arujiki (facilitating sustenance), and alms ntadi rontedi (agricultural business). The practice of helping and mutual cooperation in Bima is a culture of alms including to 'urf which is valid and the law is permissible, because it fulfills the terms and conditions of 'urf.